2007
DOI: 10.1080/15320380701285758
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil Organic Matter on Copper Extraction from Contaminated Soil

Abstract: Column experiments of copper extraction from four contaminated soils characterized by a content of Soil Organic Matter (SOM) ranging from 1% to 25% are presented and discussed. The extraction was performed by flushing the soil with an aqueous solution of a sodium salt of ethylene diamminotetraacetic acid (EDTA). Preliminary tests were performed on a soil containing 25% of organic matter, to investigate the influence of pH, concentration and volumes of EDTA on its chelant action and on the dissolution of SOM. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…For an example, EDTA-extractable Cu was significantly greater at higher SOM content than at lower organic content. This was attributed to the formation of highly stable copper-humate complexes and to their increasing dissolution that occurred in the soils with higher organic matter level (Di Palma et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…For an example, EDTA-extractable Cu was significantly greater at higher SOM content than at lower organic content. This was attributed to the formation of highly stable copper-humate complexes and to their increasing dissolution that occurred in the soils with higher organic matter level (Di Palma et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors (Boudesocque et al, 2007;Cheshire et al, 1994;Flogeac et al, 2004) have shown that Cu(II) interacts with the soils and forms "innersphere" complexes where Cu(II) replaces some hydration water molecules of the functional groups, thus forming very stable complexes with the soils, since there is direct coordination between the metal and the functional groups (Palma et al, 2007;Wu et al, 2001). On the other hand, it is likely that Cu(II) forms "outer-sphere" complexes with the biosolid, since the FTIR spectra (Fig.…”
Section: Behavior Of Copper On the Mcpesmentioning
confidence: 95%
“…The significant correlation between extractable Cu and soil organic matter might be attributed to the formation of highly stable copper-humate complexes and to their increasing dissolution that occurred in the soils (Di Palma et al 2007).…”
Section: Discussionmentioning
confidence: 99%